Energy Management Strategies for Dwellings with Photovoltaic Production - Le, Minh Hoang (Old Journal, 2017)
Homes and offices are key elements in the sustainable urban development because they consume a large part of the electricity production in European countries. Because of the increasing part of renewable energy in electricity production, which is difficult to control, consumers will have to become more involved in the grid management by not only reducing but also by adjusting their consumption in order to reach equilibrium between production and consumption on the grid, on one hand, and to limit the use of production means with high emission of CO2 on the other hand. In this paper we present a decision system that provides an active demand side management solution. This decision system is based on the weather forecasts and a variable cost of electricity. This paper states the problem of energy management in buildings and describes the optimization problem defined to adjust the energy consumption of buildings to local production constraints.